1981
DOI: 10.1002/hlca.19810640213
|View full text |Cite
|
Sign up to set email alerts
|

Selektive Umfunktionalisierung der terminalen Amidgruppe offenkettiger Polyamide via 2‐Oxazolin‐5‐one als Zwischenstufen. Vorläufige Mitteilung

Abstract: Selective Modification of the Terminal Amide Group of Linear Polyamides via 2-0xazolin-5onesas Intermediates SummaryTreatment of aqueous or alcoholic solutions of diamides of type 2 with HC1 leads to the formation of amide-acids and amide-esters of type 3 (Scheme I and Table). It has been shown, that 2-oxazolin-5-ones of type 4 are intermediates of this selective transformation of the disubstituted terminal amide group. The selectivity of the transformation is demonstrated by the reaction sequence shown in The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The amide moiety of the products could conveniently be converted to an ester or amine (Scheme ). The ester conversion was accomplished by the oxazolone procedure of Heimgartner . Deprotection of the sulfinyl group of 21 and subsequent N-benzoylation afforded diamide 37 .…”
mentioning
confidence: 99%
“…The amide moiety of the products could conveniently be converted to an ester or amine (Scheme ). The ester conversion was accomplished by the oxazolone procedure of Heimgartner . Deprotection of the sulfinyl group of 21 and subsequent N-benzoylation afforded diamide 37 .…”
mentioning
confidence: 99%
“…Hydrolytic cleavage of bulky disubstituted imidazolidinones can be quite problematic, particularly for substituents larger than methyl on the phenylglycine system (ref a,b). The structural requirements for our compounds were not tolerant of these conditions.…”
Section: Referencesmentioning
confidence: 99%
“…The initial synthetic implementation of our strategy utilized the N -benzoyl-protected imidazolidinone; however, we encountered problems with the extreme conditions needed to hydrolyze the benzoyl group of the dialkylated N -benzoyl-imidazolidinones. , To circumvent this problematic cleavage, we sought to explore the “unprotected” imidazolidinone 13 (Scheme ). ,
3 Alkylation of Imidazolidinone 13
…”
mentioning
confidence: 99%
“…We became interested in 1,3‐oxazol‐5(4 H )‐ones as intermediates in the ‘azirine/oxazolone method’ for the synthesis of peptides containing α , α ‐disubstituted α ‐amino acids . It has been shown that peptides of type 1 with a C‐terminal Aib‐amide on treatment with HCl in toluene at elevated temperature form 1,3‐oxazol‐5(4 H )‐ones 2 , which in the presence of nucleophiles spontaneously react under ring opening to give, e.g ., esters 3 [a][6c][6d] ( Scheme ). Furthermore, it was proposed that the DCC‐coupling of peptides containing a terminal Aib‐acid with amino acid esters 4 leads to peptides 5 via an intermediate 1,3‐oxazol‐5(4 H )‐one 2 [b – 6e] ( cf .…”
Section: Introductionmentioning
confidence: 99%